Artists' studios (Revista Apotheke, 2025)
This article reflects on the difference between visiting an artist’s studio and visiting its recreation in a museum, and between seeing a work in the artist’s studio and experiencing it in a museum space. It takes as its starting point the transposition of three artists’ studios into museum spaces: Piet Mondrian’s studio at the 22nd São Paulo Biennial in 1994; Jackson Pollock’s studio at MoMA in New York, on the occasion of his retrospective exhibition in 1998; and Francis Bacon’s studio at The Hugh Lane Gallery in Dublin, opened to the public in 2001. The text also makes some observations about changes that the space where artists work has undergone over time in the West since the Renaissance, and how this is represented by the terms most commonly used today: atelier, which refers to carpentry workshops, spaces open to visitors and populated by apprentices and assistants; and studio, originally a place reserved and dedicated to study.
Keywords: studio; painting; modern art; museum; creative process